CONFLICT CONCERNS EXPLORED IN THE FILM "THE BATMAN" 2022 DIRECTED BY MATT REEVES - Poppy Dwi Nurasil (Journal of Linguistica, 2024)
This dissertation explores the theme of conflict depicted in the 2022 film "The Batman". The movie centers around a character known as The Riddler, who has murdered several officials in Gotham City and exposes their hidden, darker sides, leading to conflicts with various factions. Conflict, defined as disagreement stemming from differing viewpoints, is the focal point of this analysis. The objective of this study is to delineate the types of conflicts portrayed by the antagonists and to elucidate the resultant impacts. To achieve this, a sociological approach was adopted, supplemented by two theoretical frameworks: Nina Genneby and Ruben Markosyan's theory, and Kun Maryati and Juju Suryawati's theory. Additionally, a descriptive qualitative research methodology was employed to dissect the film. The findings reveal two primary types of conflict: interpersonal and inter-group conflict. Furthermore, seven positive consequences are identified, including enhanced internal solidarity, the fostering of intriguing inter-group dynamics, mobilization of previously passive citizens, the emergence of resilient individuals, stimulation of innovation, facilitation of evaluation, and the formulation of new compromises. Conversely, four negative repercussions are observed, such as the rupture of personal relationships and group cohesion, property damage and loss of life, alterations in individual behavior, and the potential for domination by the victorious faction.